SISTEM INFORMASI CUSTOMER HISTORY PADA ACE HARDWARE JAMBI PRIMA MALL: Database;Information System;Customer History;PHP;PhpMyAdmin. - Puspitorini, Sukma; Jannah Vemi Putri, Miftahul (JURNAL AKADEMIKA, 2022)
The customer service staff at the Ace Hardware Jambi Prima Mall company with one of the job desks is managing the customer database used for marketing strategy, the customer database management is not effective because it still uses the manual method from the desktop application at the company by typing into Microsoft Excel. The purpose of this Customer History Information System practical work report is to make the effectiveness of the work of customer service staff to manage customer databases using case study research methods, developing this website application using the PHP programming language and the phpMyAdmin database. The pages in this application are input, process, and output, for the input needed in this application is customer data and transaction data with promo blast data processing then WhatsApp blast status. Which of the previous inputs and processes will produce reports or outputs of customers who have registered as members or have not become members, how many according to the selected period, as well as transaction data and other processes from research conducted to make it easier for customer service staff to manage the data.